Conceiving, compiling, publishing and exploiting the “Icelandic 16-electrode EHG database” - Ásgeir Alexandersson 1984- (2014)
Biomedical engineering is the application of engineering principles to biology and medicine, with the goal of improving the quality and effectiveness of patient care. Better understanding of the mechanisms underlying labor can contribute to preventing preterm birth, which is the main cause of mortality and morbidity in newborns. Studies on the electrohysterogram (EHG) have shown promising results regarding preterm labour prediction as well as other uses in obstetric care. A 16 electrode recording system in a 4-by-4 configuration on the abdomen can provide information on the propagation of uterine electrical activity. One of the main problems for researchers studying new technology is a shortage of data to enable analysis and hypothesis testing. In this respect, public access databanks are becoming increasingly important. A new category of scientific article, the Data Descriptor, has been designed to provide detailed descriptions of databases to maximize interpretation, search and reuse of the data. The main aim of this MSc project was to implement public access to 16-electrode EHG data recorded in Iceland. The second aim was to demonstrate the type of research that can be done using the database by studying the relationship between maternal clinical factors and the frequency components of contractions. The thesis describes the process of collecting, converting, annotating and de-identifying the 122 EHG recordings performed by the author between 2008 and 2010. The now publicly available Icelandic 16-electrode EHG database, found at PhysioNet, is then presented along with its Data Descriptor. The study on clinical factors and EHG data from the database suggests that a pregnant woman’s body mass index, age and obstetric history may influence frequency components of contractions. This could have implications for the development of a medical device for predicting preterm labour and at the same time demonstrates the use that can be made of the database. Biomedical engineering Electrohysterogram Preterm birth Database ...